Rock glacier inventory of the western Nyainqêntanglha Range, Tibetan Plateau, supported by InSAR time series and automated classification - Reinosch, Eike; Gerke, Markus; Riedel, Björn; Schwalb, Antje; Ye, Qinghua; Buckel, Johannes (Permafrost and Periglacial Processes, 2021)
The western Nyainqêntanglha Range on the Tibetan Plateau reaches an elevation of 7,162 m and is characterized by an extensive periglacial environment under semi-arid climatic conditions. Rock glaciers play an important part of the water budget in high mountain areas and recent studies suggest that they may even act as climate-resistant water storages. In this study we present the first rock glacier inventory of this region containing 1,433 rock glaciers over an area of 4,622 km. To create the most reliable inventory we combine manually created rock glacier outlines with an automated classification approach. The manual outlines were generated based on surface elevation data, optical satellite imagery and a surface velocity estimation. This estimation was generated via InSAR time series analysis with Sentinel-1 data from 2016 to 2019. Our pixel-based automated classification was able to correctly identify 87.8% of all rock glaciers in the study area at a true positive rate of 69.5%. In total, 65.9% of rock glaciers are classified as transitional with surface velocities of 1–10 cm/yr. In total, 18.5% are classified as active with higher velocities of up to 87 cm/yr. The southern windward side of the mountain range contains more numerous and more active rock glaciers. We attribute this to higher moisture availability supplied by the Indian Monsoon.